2018
DOI: 10.1021/acs.joc.7b02815
|View full text |Cite
|
Sign up to set email alerts
|

Three Sequential C–N Bond Formations: tert-Butyl Nitrite as a N1 Synthon in a Three Component Reaction Leading to Imidazo[1,2-a]quinolines and Imidazo[2,1-a]isoquinolines

Abstract: tert-Butyl nitrite serves the dual role of an oxidant as well as a N1 synthon in a multicomponent reaction involving quinolines, isoquinolines, and styrenes. Herein, two sp C-H functionalizations of styrenes and one sp C-H functionalization of quinolines and isoquinolines lead to the formation of fused quinolines and isoquinolines via three sequential C-N bond formations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…prop-2-ene-1,1,3triyltriaryl system gave exclusively a mono nitro product where the nitro group is at the benzylic position (α-carbon) (Scheme 1f ). Surprisingly, compared to all other previous results [5][6][7] this is an unusual attacking position for the nitro group as it always prefers to attack at the -position (Scheme 1a-d). [11] Styrenes react with TBN in an oxygen atmosphere to givenitro alcohols and their nitrate derivatives, where the exclusive attack of the NO 2 group is at the terminal carbon of the styrene (Scheme 1c).…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…prop-2-ene-1,1,3triyltriaryl system gave exclusively a mono nitro product where the nitro group is at the benzylic position (α-carbon) (Scheme 1f ). Surprisingly, compared to all other previous results [5][6][7] this is an unusual attacking position for the nitro group as it always prefers to attack at the -position (Scheme 1a-d). [11] Styrenes react with TBN in an oxygen atmosphere to givenitro alcohols and their nitrate derivatives, where the exclusive attack of the NO 2 group is at the terminal carbon of the styrene (Scheme 1c).…”
Section: Introductioncontrasting
confidence: 62%
“…Under a similar condition α, -unsaturated carboxylic acids and cyclic internal alkene afforded nitroalkenes. [11] During the formation of isoxazoline, [4,5] imidazo [1,2-a]quinolines, [6] and 1,2,4-oxadiazole-5(4H)-ones [7] from styrenes and TBN, the in situ generated NO 2 radical attacks at the -carbon while the NO radical attacks at the α-carbon even though both the radicals coexist in the medium. From the computational calculation, it was found that the attack of NO 2 radical at the terminal carbon that is at the -carbon is stabilised by around 6 kcal/mole less than the attack by NO radical at the same site.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the intermediates were detected by HRMS analysis. The present methodology was successfully applied for the synthesis of 4‐((2‐phenylimidazo[2,1‐ a ]isoquinolin‐3‐yl)methyl)morpholine hydrochloride that possesses a significant range of biological activities (Scheme ) …”
Section: Outlines Of the Reactions Involving Tbnmentioning
confidence: 99%
“…Initially,T BN oxidizes alkenyl oxime (129) The nitrile group is au biquitous functional group in synthetic organic chemistrya nd can be easily used form any functional group conversions. Wang and co-workers reported the synthesis of aromatic nitriles( 132)v ia ap alladium-catalyzed ammoxidation of methyl arenes (131) using tert-butyl nitrite (TBN) and N-hydroxyphthalimide (NHPI) where TBN simultaneously acts both as the nitrogen source as well as an oxidant (Scheme 97). [126] In 2016, Song and co-workers reported the synthesis of aryl nitrilesf rom aryl acetylenes.…”
Section: Oximationmentioning
confidence: 99%
See 1 more Smart Citation